EFFECT OF IRRIGATION METHODS AND MAGNETIZATION OF WATER ON QUALITY OF SUNFLOWER AND WATER USE EFFICIENCY - & Abdul-Razaq, Yahya (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This experiment was carried out at the experimental farm of Field Crop Department, College of Agriculture, university of Baghdad, during two spring seasons of 2012 and 2013 to study the response of quality characteristics of sunflower cultivar Akmar to the irrigation methods and water of magnetization technology and water use efficiency. The experiment was laid out as a split plot in randomized complete block design (RCBD) with three replications. Four irrigation methods were used as main plots, [Farrow irrigation (I1), unfixed alternate furrow irrigation (I2), fixed alternate furrow irrigation (I3) and basin irrigation (I4)], while four levels of magnetized water (0, 1000, 2000 and 3000) Gauss were used as sub plot treatments. The results revealed that unfixed alternate furrow irrigation method could reduce irrigation water by 40 %, and it was irrigation water reduced from 425 to 255 mm per season in 2012th season and reduced from 364 to 234mm per season in 2013 season were an increment of water use efficiency (WUE) by 63.5% and 61.4% were accrued during growing seasons respectively in comparison with full irrigation treatment (I1). The Leaves potassium content decreased by14.4 to 5.8% for both seasons respectively. No significant effect was detected between I1 and I2 in qualitative traits except reduction in oil percentage as it reaches 6.3 to 8.8% in both seasons respectively. Results displayed a positive effect of using magnetized irrigation water on all measured traits. WUE increased by 45.1 to 56 %, nitrogen leaf content by 19.6 and 4.8% , phosphor leaves content by 35.1 and 41.7%, potassium leaves content by 20.7 and 10.8%, chlorophyll content by 4.5 to 7.6%, seed oil content by 5.0 to 5.6%. Interaction relations between experiment treatments were significant in some of studded traits.